A study of 2-stroke marine diesel engine characteristic based on condition based maintenance - Awang, Mohd Naim (2015)
In today’s environment, generating revenues for any industry is important. Profit margins are shrinking and often the difference between a profit and a loss can be as simple as preventing loss and improving efficiencies. Locating sources of energy waste, identifying failure conditions in electrical and mechanical systems all contribute to helping improve the bottom line. The ability of a vessel to operate depends on the ability of the ship main propulsion produces optimum power and translated through the transmission system to the propeller shaft. Marine diesel engine is the prime mover, which is synonymous in the shipping industry. Most important of criterion for boost the profit margin are the reliability, availability, repair, installation costs, operating costs, flexible and engine size. Failure to optimize the performance of the engine will tremendously reduce the profit margin. The condition based maintenance (CBM) is the option for engine’s owner to gain the profit margin with shrinking the performance of the engine. CBM is the new method for performing maintenance and it was applied in various industries such as aviation industries, marine industries and commercial sector. Wave spectrum analysis using Ultrasonic wave sensor is one of the CBM method that can be applied for early identifying the excessive friction. In this study, both condition based maintenance and wave spectrum analysis be utilized together for identifying the engine performance without involving major and complex procedure. This study approved that once the engine is operating within the operating limit (maximum exhaust gas temperature is 350˚C, maximum inlet lubricating oil temperature is 55˚C and maximum inlet fuel oil temperature is 50˚C.) and that wave spectrum show the decrement of wave amplitude, the engine is in good condition and no major maintenance required. If the working parameter is out of the range, and significant friction detected using wave spectrum analysis, then the maintenance is required. Therefore, both condition based maintenance and wave spectrum analysis is a good combined method to identify the engine performance and able to reduce the maintenance cost that using the conventional maintenance schedule.